Measurement of proton tunneling in short hydrogen bonds in single crystals of 3,5 pyridinedicarboxylic acid using nuclear magnetic resonance spectroscopy - Frantsuzov, Ilya; Ford, Samantha J.; Radosavljevic-Evans, Ivana; Horsewill, Anthony J.; Trommsdorff, Hans Peter; Johnson, Mark R. (American Physical Society, 2014)
In this letter, we present NMR spin-lattice and relaxometry data for proton transfer in one of the shortest known N-H∙∙∙O hydrogen bonds in a single crystal of 3,5 pyridinedicarboxylic acid (35PDCA). It is widely believed that proton transfer by quantum tunnelling does not occur in short hydrogen bonds since the ground state energy level lies above the potential barrier yet this data shows a temperature independent, proton tunnelling rate below 77 K and a clear deviation from classical dynamics below 91 K. This study therefore suggests that proton tunnelling occurs in all hydrogen bonds at low temperature and the cross-over temperature to classical hopping must be determined when evaluating whether proton tunnelling persists at higher temperature, for example in enzyme catalysis under physiological conditions.